2022
DOI: 10.3389/fenvs.2022.954004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tillage management on the wind erosion of arable soil in the Chinese Mollisol region

Abstract: Wind erosion is a serious problem in agricultural regions and threatens the regional food production in Northeast China. However, limited information is available on the characteristics of wind erosion in arable soil in Northeast China. As a result, field-based research during periods of vulnerability to wind erosion is essential. This study quantified the characteristics of soil wind erosion under no-tillage (NT) and conventional tillage (CT) treatments in China’s northern “corn-belt.” The results determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…The use of polyacrylamide (PAM) to form shells on soil surfaces has also been developed [40,41]. Agricultural measures like no tillage [42,43], ridge [44,45], and vertical tillage [43] have been implemented to improve soil structure and enhance soil roughness as a means of preventing wind erosion.…”
Section: Development Of Wind Erosion Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of polyacrylamide (PAM) to form shells on soil surfaces has also been developed [40,41]. Agricultural measures like no tillage [42,43], ridge [44,45], and vertical tillage [43] have been implemented to improve soil structure and enhance soil roughness as a means of preventing wind erosion.…”
Section: Development Of Wind Erosion Researchmentioning
confidence: 99%
“…Changes in precipitation and temperature directly affect the soil conservation f unction of the ecosystem [115,116]. Many studies have demonstrated the stimulating effect of temperature and wind speed on wind erosion [42,107,117], while precipitation has a mitigating effect on wind erosion [118,119]. In recent years, global warming has exacerbated soil dryness and led to an increase in soil temperature [120].…”
Section: Implications For Wind Erosion Researchmentioning
confidence: 99%